2012
DOI: 10.1089/g4h.2012.0019
|View full text |Cite
|
Sign up to set email alerts
|

Concept Software Based on Kinect for Assessing Dual-Task Ability of Elderly People

Abstract: The DTTC test quantitatively evaluates a compound function including DT, balance, and cognitive abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…With a focus on DT, we developed a new concept called the Dual-Task Tai Chi (DTTC) test [ 8 ]. This system was developed using Kinect (Microsoft, Redmond, WA, USA), a motion-capture device, and demonstrated that the DTTC test quantitatively evaluates compound functions, including DT, balance, and cognitive abilities in elderly people [ 9 ]. In unpublished data, we found that DTTC training was useful not only to assess but also to improve balance and mobility among elderly people [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With a focus on DT, we developed a new concept called the Dual-Task Tai Chi (DTTC) test [ 8 ]. This system was developed using Kinect (Microsoft, Redmond, WA, USA), a motion-capture device, and demonstrated that the DTTC test quantitatively evaluates compound functions, including DT, balance, and cognitive abilities in elderly people [ 9 ]. In unpublished data, we found that DTTC training was useful not only to assess but also to improve balance and mobility among elderly people [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This simple feedback makes it almost impossible to discern the specific corrections required in each posture. The Dual-Task Tai Chi game suffers from similar limitations, but with more interesting game play [23], using Kinect T M -based full-body control with a cognitive task, i.e., 4x4 Sudoku. In this game, the user has to reach a specific posture in order to select a number with the right hand or foot, and then place this number on the Sudoku grid with the left hand or foot.…”
Section: Related Research and Backgroundmentioning
confidence: 99%
“…The DTTC test [8][9][10] requires users to solve a number placement problem (Sudoku) by controlling a stick figure with the movement of their entire body. The user's full-body motion is captured using Kinect and is translated into movements for the stick figure on a screen.…”
Section: B Devicementioning
confidence: 99%